KONTRIBUSI SPIRITUALITAS KESEHATAN MENTAL PADA REMAJA - Nilam Irma Damayanti; Nasichah, Puspa Isya Qoblia, Agus Supriyono (Jurnal Komunikasi, 2023)
This study aims to determine the importance of spirituality in improving mental well- being through the perspective of Islamic religion in adolescents aged 17 to 25 years who are Muslims and have awareness about mental health. The research method used is quantitative research by filling out a questionnaire through Google Form, which is used to obtain an overview of the importance of having high spirituality in improving mental well-being. The results of the data will be seen through the answers contained in the questionnaire by using the theory from previous research. This research can benefit individuals in improving their mental well-being through spiritual practices that are in accordance with their religious beliefs